Beyond Hadoop. - Mone, Gregory (Communications of the ACM, 2013)
The article focuses on open source processing frameworks and real-time computing systems. It comments on the Apache Hadoop software system which uses computer clusters to process large datasets and talks about how online music service Pandora uses Hadoop to analyze data on skipped songs and listener ratings through machine learning, collective intelligence tasks and collaborative filtering. It mentions search engine company Google's distributed data system, Google File System (GFS), and MapReduce which allows jobs to be broken into smaller pieces and sent to different computers. It states that Hadoop uses two software modules, one a file system similar to GFS which disperses large datasets on multiple computers, and Hadoop MapReduce which splits up and analyzes mined data.